Tuning the Functionality by Splicing: Factor H and Its Alternative Splice Variant FHL-1 Share a Gene but Not All Functions - Mannes, Marco; Dopler, Arthur; Huber-Lang, Markus; Schmidt, Christoph Q. (Frontiers in Immunology, 2020)
The alternative pathway regulator Factor H-like protein 1 (FHL-1) is composed of the first 7 N-terminal complement control protein domains of Factor H (FH) and protects host surfaces from uncontrolled complement attack. Although FHL-1 shares the N-terminal regulatory domains with FH, it was thought to be a weaker regulator. Recently, the regulatory activity of FHL-1 was shown to be comparable to FH. Nonetheless, the question remained whether FHL-1 is an indispensable, unique regulator. The discovery that FHL-1 is the predominant regulator on Bruch’s membrane, a critical site for the onset and progression of age-related-macular degeneration (AMD), showed that FHL-1 is essential for complement regulation. A common single nucleotide polymorphism in FH/FHL-1 that predisposes for AMD underlines the important role of FHL-1 in this context. Reports that some cancer tissues specifically upregulate FHL-1 expression, thereby evading immune surveillance, suggests a pronounced regulatory activity of the splice variant. Several microorganisms specifically recruit FHL-1 to evade complement attack. From a phylogenetic point of view, FHL-1 appears much later than other complement regulators, which could imply a specific role that is possibly not systemic but rather tissue specific. This review focuses on the current knowledge of FHL-1 and its physiological and pathophysiological roles.